NiONPs-induced alteration in calcium signaling and mitochondrial function in pulmonary artery endothelial cells involves oxidative stress and TRPV4 channels disruption. Issue 1 (2nd January 2022) - Germande, Ophélie; Baudrimont, Magalie; Beaufils, Fabien; Freund-Michel, Véronique; Ducret, Thomas; Quignard, Jean-François; Errera, Marie-Hélène; Lacomme, Sabrina; Gontier, Etienne; Mornet, Stéphane; Bejko, Megi; Muller, Bernard; et al.
Abstract: In New Caledonia, anthropic activities, such as mining, increase the natural erosion of soils in nickel mines, which in turn, releases nickel oxide nanoparticles (NiONPs) into the atmosphere. Pulmonary vascular endothelial cells represent one of the primary targets for inhaled nanoparticles. The objective of this in vitro study was to assess the cytotoxic effects of NiONPs on human pulmonary artery endothelial cells (HPAEC). Special attention will be given to the level of oxidative stress and calcium signaling, which are involved in the physiopathology of cardiovascular diseases. HPAEC were exposed to NiONPs (0.5–150 μg/cm 2 ) for 4 or 24 h. The following different endpoints were studied: (i) ROS production using CM-H2 DCF-DA probe, electron spin resonance, and MitoSOX probe; the SOD activity was also measured (ii) calcium signaling with Fluo4-AM, Rhod-2, and Fluo4-FF probes; (iii) inflammation by IL-6 production and secretion and, (iv) mitochondrial dysfunction and apoptosis with TMRM and MitoTracker probes, and AnnexinV/PI. Our results have evidenced that NiONPs induced oxidative stress in HPAEC. This was demonstrated by an increase in ROS production and a decrease in SOD activity, the two mechanisms seem to trigger a pro-inflammatory response with IL-6 secretion. In addition, NiONPs exposure altered calcium homeostasis inducing an increased cytosolic calcium concentration ([Ca 2+ ] i ) that was significantly reduced by the extracellular calcium chelator EGTA and the TRPV4 inhibitor HC-067047. Interestingly, exposure to NiONPs also altered TRPV4 activity. Finally, HPAEC exposure to NiONPs increased intracellular levels of both ROS and calcium ([Ca 2+ ] m ) in mitochondria, leading to mitochondrial dysfunction and HPAEC apoptosis.